Risk of Mandibular Angle Fracture and Its Co-relation to Absence/Presence,Type of Mandibular Impacted 3rd molar; A Retrospective and Prospective Study - Barman, Anusmita; Tandon, Sapna; Wadhwani, Puneet; S .Borse, Shraddha; Chakravarty, Chinmoy; Gaffar, Mo Adil (Journal of Neonatal Surgery, 2025)
Introduction: The study is designed to evaluate the influence of presence ,eruption status and position of mandibular third molars on mandibular angle fracture. Materials and Methods: A retrospective and prospective study design and a sample composed of panoramic radiographs of 80 patient and CT scan wherever needed . The predictor variables were the presence and position of impacted 3rd molar. 3rd molar position was grouped in categories based on the Pell and Gregory classification. The outcome variable was the presence of an angle fracture and commonly associated with types and position of impacted 3rd molar and also the nature of fracture . Results: Of total 79 sample of mandibular angle fracture44(55.7% )mesioangular, 17(21.5%)vertical,10 (12.7%)horizontal and 8(10.1%) distoangular impacted 3rd molar are associated. Also revealed that incidence of angle fracture were high in patients with impacted 3rd molar with position B 28(35.4%) and position A 23(29.1%) have high incidence of angle fracture in the study. About the nature of the fracture , out of total 44 all 44(100%) mesioangular impacted 3rd molar caused horizontal unfavourable fracture. 39(88.8%) caused vertical unfavourable fracture and rest 5(11.5%) caused vertical favourable fracture Conclusion: The mandibular angle with an impacted third molar tooth is comparatively weaker than the angle region without an impacted tooth. The chances of angle fracture in superficially erupted mandibular third molar is higher than those with a deeply impacted 3rd molar.The study results conclude that patients with mesioangular positionB impacted 3rd molar present in the mandible comparatively increased risk for angle fractures.